Prompt y-ray activation analysis of Martian analogues at the FRM II neutron reactor and the verification of a Monte Carlo planetary radiation environment model - Skidmore, M.; Ambrosi, R.; Vernon, D.; Calzada, E.; Benedix, Gretchen; Bucherl, T.; Schillinger, B. (Elsevier, 2009)
Planetary radiation environment modelling is important to assess the habitability of a planetary body. It is also useful when interpreting the γ-ray data produced by natural emissions from radioisotopes or prompt γ-ray activation analysis. γ-ray spectra acquired in orbit or in-situ by a suitable detector can be converted into meaningful estimates of the concentration of certain elements on the surface of a planet. This paper describes the verification of a Monte Carlo model developed using the MCNPX code at the University of Leicester. The model predicts the performance of a geophysical package containing a γ-ray spectrometer operating at a depth of up to 5 m. The experimental verification of the Monte Carlo model was performed at the FRM II facility in Munich, Germany. The paper demonstrates that the model is in good agreement with the experimental data and can be used to model the performance of an in-situ γ-ray spectrometer.